Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas X Materi SPLDV Ditinjau dari Adversity Quotient (AQ) - Sriyanti Wulandari; Ali Shodiqin; Dewi Wulandari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mathematics plays a crucial role in developing students' problem-solving abilities and independence. Educators need to consider the varying characteristics of students when it comes to solving problems, one of which is their adversity quotient (AQ) level. The adversity quotient relates to a student's ability to handle complex problems or to overcome challenging situations. This research aims to analyze the mathematical problem-solving abilities of Class X students in the context of Systems of Linear Equations in Two Variables (SPLDV) based on their Adversity Quotient (AQ). This qualitative, descriptive study involved selecting research subjects using an AQ questionnaire and was conducted in Class X. Data collection methods included testing, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that subjects with the Climber type can understand problems, develop problem-solving plans, solve problems with accurate and appropriate steps, and use available information to re-check their answers. Subjects with the Camper type can understand problems, develop problem-solving plans, solve problems with accurate and appropriate steps, but often cannot use available information to re-check their answers. Subjects with the Quitter type can understand the problem and formulate a plan but struggle to solve the problem accurately and appropriately, and tend not to use available information to re-check their answers.